INVERTENDO A SALA DE AULA INVERTIDA: UMA PROPOSTA UTILIZANDO A METODOLOGIA DA RESOLUÇÃO DE PROBLEMAS NO ENSINO DE MATEMÁTICA - Ramos, Rafaeli (2021)
This study was initially motivated by concerns about teaching and learning in Mathematics, as we found that there are many difficulties and limitations. One of the ways to contribute to the improvement is to rethink the way of teaching Mathematics, so the present work was dedicated to the implementation of the Problem Solving methodology allied to the Inverted Classroom method. The inspiration for this research came when we found a study done at Stanford University that proposes “flip the flipped classroom”, authors Blikstein and Schneider claim that presenting a subject in a practical way can be more practical. effective than starting with theory. The experiment was carried out in a public school in the city of Guarapuava/PR, in a class of the 3rd year of high school. As a guiding question we have: "What are the impacts on the teaching and learning of Mathematics when the Problem Solving Methodology is used as a starting point for the application of the Flipped Classroom?" and as a general objective “To analyze the possible contributions to the teaching and learning of Mathematics when the contents are worked using the Problem Solving Methodology allied to the Inverted Classroom method”. In the theoretical framework, the main researchers who supported this study were Polya (1945), Onuchic (1999), Bergmann and Sams (2012) and Schmitz (2016). The nature of the research is qualitative and followed the method of direct observation to the participant. From the data collected through interviews, questionnaires and notes in the logbook, five categories emerged with the function of answering the guiding question and achieving the general objective. Finally, the analysis and interpretation of the data followed the proposal by Bogdan and Biklen (1994), that is, the triangulation between the collected data, the theory and the researcher's perception. The results of this research indicate that the students gradually developed autonomy, becoming the center of the teaching and learning process, the teacher's role changed from authoritarian to mediator and there was a change in the way mathematical contents were approached, because in this practice the students had contact with a generative problem showing the applicability of the topic before the theory.